Why does leader aggressive humor lead to bystander workplace withdrawal behavior?—Based on the dual path perspective of cognition- affection - Chen, Hao; Wang, Liang; Bao, Jiaying (Frontiers in Psychology, 2022)
Based on Cognitive-Affective Personality System Theory, this study takes 443 employees of several Chinese enterprises and their direct superiors as the research objects, then a 1:1 paired survey is carried out at three different time points. this study found from a bystander perspective: leader aggressive humor plays a positive role on bystander affective rumination and bystander workplace anxiety. Both bystander affective rumination and bystander workplace anxiety play a mediation role between leader aggressive humor and bystander workplace withdrawal behavior.Besides, organization-based self-esteem alleviates the positive impact of leader aggressive humor on bystander affective rumination and bystander workplace anxiety, and then moderates the indirect impact of leader aggressive humor on bystander workplace withdrawal behavior through bystander affective rumination and bystander workplace anxiety respectively. This study has practical guiding significance for promoting the organization to reduce the occurrence of aggressive humor, helping employees better integrate into the organization and building a harmonious organizational environment.